The International Classification of Functioning Disability and Health Framework (ICF): a new approach to enhance sport and physical activity participation among people with disabilities in Scotland - Carlin, Liz; McPherson, Gayle; Davison, Richard (Frontiers in Sports and Active Living, 2024)
This research provides a pilot study of the International Classification of Functioning Disability and Health Framework (ICF) involving persons with disabilities (PWD) with and without lived experience of sport participation in Scotland. National surveys in Scotland provide limited information on the nature of individual disability restricting the understanding of the relationship between disability and sport and physical activity participation. The ICF is a framework that aims to describe and classify functioning and thus can be used as a tool to provide a more detailed description of impairment for PWDs beyond their clinical condition. This knowledge has the potential to enhance the development of policies to increase the participation levels in this group. The ICF has also been used to inform the current IPC classification system at a competitive and elite level. As part of a larger study, 450 participants aged between 12 and 70 years completed an online questionnaire examining attitudes to, and participation in, sport and physical activity as well as completing the structural and functional components of the ICF. Subsequently, 18 people participated in focus groups aged between 13 and 61 years. The focus groups examined four meta-theme areas: physical, social, psychological, and sport-specific factors. The results confirm that the ICF provided a more detailed indicator of the key impairments that could have an impact on sport and physical activity participation. There was a clear lack of awareness of the links between the ICF and the classification system for competitive parasport. We concluded that a modified ICF-based assessment tool, incorporating social and environmental factors, has the potential to predict the likelihood of participation and offers a more comprehensive picture of both individual and national disability characteristics. This allows for the development of targeted policies and strategies to assist those with a disability to participate in sport. The overall framework presents a shift in thinking, in policy terms, for those in public health and in sport governance and delivery. The significance of this work is especially concerned with public health and wellbeing and sport development policy as pathways from recreational sport user to elite athlete parasport classification and performance.